1998
DOI: 10.1093/occmed/48.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and sensitization in bread and cake bakers

Abstract: This purpose of this study was to examine the relationship between exposure to wheat flour, soya flour and fungal amylase and the development of work-related symptoms and sensitization in bread and cake bakery employees who have regular exposure to these substances. The study populations consisted of 394 bread bakery workers and 77 cake bakery workers whose normal jobs involved the sieving, weighing and mixing of ingredients. The groups were interviewed with the aim of identifying the prevalence, nature and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…We found that 43% of bakers reported work-related respiratory symptoms, similar to levels found in a recent study of small bakeries in Scotland [Jeffrey et al, 1999] but higher than levels found in a recent UK-based study of supermarket bakeries and levels previously reported in British bakeries [Musk et al, 1989;Smith and Smith, 1998]. There was no significant difference in prevalence of upper or lower respiratory symptoms in bakeries classified by size, suggesting that interventions aimed at reducing work-related symptoms in this group of workers should focus on all bakeries independent of size.…”
Section: Discussionsupporting
confidence: 85%
“…We found that 43% of bakers reported work-related respiratory symptoms, similar to levels found in a recent study of small bakeries in Scotland [Jeffrey et al, 1999] but higher than levels found in a recent UK-based study of supermarket bakeries and levels previously reported in British bakeries [Musk et al, 1989;Smith and Smith, 1998]. There was no significant difference in prevalence of upper or lower respiratory symptoms in bakeries classified by size, suggesting that interventions aimed at reducing work-related symptoms in this group of workers should focus on all bakeries independent of size.…”
Section: Discussionsupporting
confidence: 85%
“…Although in the bakery occupational exposure could elicit sensitizations to bakery allergens and WRS, those only occur in a small fraction of bakery workers [19,20], which was consistently found in the present study (7.4 and 13.1%, respectively). This common finding could explain the lack of associations among serum S100A8 as well as S100A9 levels and those parameters.…”
Section: Discussionsupporting
confidence: 83%
“…Although cross sectional studies among bakers have shown a high prevalence of asthma-like symptoms, [10,30,31] the relationship between sensitisation and asthma-like symptoms, so far, seems to be unclear [8,10,11,13,30,32,33]. Asthma-like symptoms may progress to asthma [34] but the natural history of this symptom in defined populations has not been studied in great detail.…”
Section: Respiratory Symptoms In Baker Apprentices T Skjold Et Almentioning
confidence: 99%
“…In one cross-sectional study, a close relationship was found between respiratory symptoms and sensitisation [8]. However, other studies have shown that a high proportion of work-related symptoms have no allergic basis and are the result of a direct response to a dusty environment [10][11][12][13][14][15].…”
mentioning
confidence: 98%